Antibiotic Potentiators Against Multidrug-Resistant Bacteria: Discovery, Development, and Clinical Relevance - Chawla, Meenal; Verma, Jyoti; Gupta, Rashi; Das, Bhabatosh (Frontiers in Microbiology, 2022)
Antimicrobial resistance in clinically important microbes has emerged as an unmet challenge in global health. Extensively drug-resistant bacterial pathogens have cropped up lately defying the action of even the last resort of antibiotics. This has led to a huge burden in the health sectors and increases morbidity and mortality rate across the world. The dwindling antibiotic discovery pipeline and rampant usage of antibiotics has set the alarming bells necessitating immediate actions to combat this looming threat. Various alternatives to discovery of new antibiotics are gaining attention such as reversing the antibiotic resistance and hence reviving the arsenal of antibiotics in hand. Antibiotic resistance reversal is mainly targeted against the antibiotic resistance mechanisms, which potentiates the effective action of the antibiotic. Such compounds are referred to as resistance breakers or antibiotic adjuvants/potentiators that work in conjunction with antibiotics. Many studies have been conducted for the identification of compounds, which decrease the permeability barrier, expression of efflux pumps and the resistance encoding enzymes. Compounds targeting the stability, inheritance and dissemination of the mobile genetic elements linked with the resistance genes are also potential candidates to curb antibiotic resistance. In pursuit of such compounds various natural sources and synthetic compounds have been harnessed. The activities of a considerable number of compounds seem promising and are currently at various phases of clinical trials. This review recapitulates all the studies pertaining to the use of antibiotic potentiators for the reversal of antibiotic resistance and what the future beholds for their usage in clinical settings.